Antiferroelectric single crystal of La0.011Pb0.984(Lu1/2Nb1/2)O3 with high energy storage density. Issue 8 (June 2016) - Yang, Xiaoming; He, Chao; Liu, Ying; Li, Xiuzhi; Wang, Zujian; Han, Shujuan; Pan, Shilie; Long, Xifa
Abstract: High quality La0.011 Pb0.984 (Lu1/2 Nb1/2 )O3 (La-PLN) antiferroelectric (AFE) single crystal was successfully obtained by a top-seed solution growth technique. The crystal structure adopts an orthorhombic phase and two sets of superlattice reflections due to B-site ordering and anti-parallel cation displacement are observed clearly and distinguished by the X-ray diffraction patterns (XRD). The Curie temperature T C is near 221 °C with a low dielectric constant (about 371). The energy storage density decreases along with the temperature increasing and the maximum energy storage density is up to 5.03 J/cm 3 at 25 °C. The results indicate that the La-PLN single crystal is a promising candidate for the AFE energy storage application.